PENANAMAN NILAI-NILAI PENDIDIKAN AKHLAK SEBAGAI UPAYA PREVENTIF TINDAKAN BULLYING DI BOARDING SCHOOL - Suci, Mutiara Nurani; Ibrahim, Rustam (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
The rise of bullying that occurs among students in Indonesia shows that currently education in Indonesia is experiencing a problem of moral decadence. To prevent further deterioration of morals in students, it is necessary to instill moral education values in students in all educational institutions, including students taking boarding school programs. By using a qualitative method approach, this research aims to find out how to instill moral education values to prevent bullying behavior in dormitories and find out what the strategies are. The results of the research show that instilling moral education values to prevent bullying behavior is carried out through an integrated boarding program between providing theory and direct practice using five strategies, namely the exemplary method, the habituation method, the advice method, the attention and supervision method and the punishment method.